SISTEM KONTROL SUHU ELECTRIC MUFFLE FURNACE MENGGUNAKAN SENSOR THERMOKOPEL TYPE-K BERBASIS MIKROKONTROLLER ARDUINO UNO - Farhan Arista Fhadillah; Asep Andang; Nundang Busaeri (Teknik Elektro Universitas Siliwangi, 2023)
Along with the development of the era, the furnace became a mandatory item in the material industry, the lack of domestic products caused the high price of heating stoves in this industry, especially in terms of learning methods, there was a need for developments in the field of technology that could make it easier, cheaper, and able to increase the productivity of human resources. Unstable temperature characteristics at high temperatures are an obstacle in this study, therefore a heater design is carried out using the PID control method. The main objective of this research is to stabilize the temperature at high temperatures at a low price. The components used in this study are Arduino Uno, Dimmer SCR 220 V 400 W, LCD, Push Button, Servo Motor, and RTC Module. To test the stability of the temperature, this research was carried out by testing the heater with empty objects in it, small objects (iron plates), and large objects (iron rods) and testing them at different temperatures, namely at 100oC, 200oC, 300oC and 400oC. From all the tests performed, the steady state error rate was not more than 5%.